Current, wave, wind and interaction induced dynamic response of a 5 MW spar-type offshore direct-drive wind turbine. (1st January 2019) - Ye, Kan; Ji, Jinchen
Highlights: Aerodynamic and hydraulic excitations as well as dynamic interactions are applied on offshore floating wind turbines. Three sea conditions, two normal and one extreme weather conditions, are considered. The effect aerodynamic and hydraulic excitations on dynamic behaviour is studied. Effect of the interaction between the drive-train system and support system is discussed. Misalignment of the sea current and wind-wave direction is examined. Abstract: This paper studies the dynamic response of a spar-type direct-drive wind turbine subjected to external and internal excitations. A free-free end model is developed for the wind turbine structure with a spar-type floating platform under deep sea condition. Firstly, the spar supported platform with tower structure is modelled as a rigid body while the nacelle is considered as a point mass attached on the top of the tower. Then the dynamic interaction between the drive-train system and the tower is considered by incorporating the modelling of a direct-drive drive-train system. The hydrodynamic and aerodynamic excitations applied include current, wave, and wind excitations as well as buoyant forces. The misalignments of the wind, wave and current are also considered to examine the induced response. With the help of the time history and FFT spectrum, the effects of both hydrodynamic and aerodynamic excitations along with the dynamic interaction between the drive-train system and tower structure on the dynamic behaviour of the spar-type floating platform are investigated under different sea conditions.